2018
DOI: 10.1038/s41467-018-06358-z
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated fires in Mediterranean Europe due to anthropogenic warming projected with non-stationary climate-fire models

Abstract: The observed trend towards warmer and drier conditions in southern Europe is projected to continue in the next decades, possibly leading to increased risk of large fires. However, an assessment of climate change impacts on fires at and above the 1.5 °C Paris target is still missing. Here, we estimate future summer burned area in Mediterranean Europe under 1.5, 2, and 3 °C global warming scenarios, accounting for possible modifications of climate-fire relationships under changed climatic conditions owing to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
242
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(259 citation statements)
references
References 71 publications
12
242
1
4
Order By: Relevance
“…The present model results also reinforced state-of-the-art restoration findings, showing that the planting of resprouting oaks in shrublands significantly redirects and accelerates the transition towards late-successional oak communities (Santana et al, 2018). Mediterranean vegetation is threatened by the expected increase in aridity due to climate change (IPCC, 2013;Guiot & Cramer, 2016;Turco et al, 2018). It was shown that increased aridity could disrupt the resilience of oak forests.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present model results also reinforced state-of-the-art restoration findings, showing that the planting of resprouting oaks in shrublands significantly redirects and accelerates the transition towards late-successional oak communities (Santana et al, 2018). Mediterranean vegetation is threatened by the expected increase in aridity due to climate change (IPCC, 2013;Guiot & Cramer, 2016;Turco et al, 2018). It was shown that increased aridity could disrupt the resilience of oak forests.…”
Section: Discussionsupporting
confidence: 82%
“…2a; Fig. Mediterranean vegetation is threatened by the expected increase in aridity due to climate change (IPCC, 2013;Guiot & Cramer, 2016;Turco et al, 2018). The mixed temporary communities could persist for a variable amount of time, partly depending on the initial oak cover (Notes S3), where low cover values could be interpreted as a proxy of oak seed availability and recruitment limitation (Sheffer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in qualitative agreement to the findings of Turco et al (2018), who showed that while modeled estimates of burned area in Mediterranean Europe increased with warming, the magnitude of such increases was substantially reduced when warming was held below 2°C above preindustrial levels. We demonstrate that policy targets to limit warming of global mean temperature to no more than 2°C above preindustrial levels have substantial implications for changes in the local FWI emergence.…”
Section: Discussionsupporting
confidence: 91%
“…The geographic extent of emergence of the four FWI metrics doubles between a 2 and 3°C warming. These results are in qualitative agreement to the findings of Turco et al (2018), who showed that while modeled estimates of burned area in Mediterranean Europe increased with warming, the magnitude of such increases was substantially reduced when warming was held below 2°C above preindustrial levels. Whereas observations suggest that changes have already occurred for aspects of fire weather metrics, these results highlight the risk avoidance for heightened fire weather conditions, fire potential, and associated fire hazards through climate mitigation efforts.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, recent extreme wildfire events, including those that occurred in 2016 in France 4 , 2017 in Spain and Portugal 5 and 2018 in Greece 6 have highlighted the limits of fire suppression capabilities under exceptional weather conditions. While previous showed that wildfire activity is expected to increase across the Mediterranean Basin because of climate change 7,8 , how the combinations of atmospheric conditions that promote large wildfires will be affected remain largely unknown and unquantified.…”
Section: Introductionmentioning
confidence: 99%